Managing and growing a cultural heritage web presence : a strategic guide - Ellis, Mike. (London : Facet, 2011)
Provides a complete guide for anyone looking to build or maintain a cultural heritage web presence. Contains data and case studies on current practice from large and small cultural heritage institutions, it advises on the best strategic approach, provides insight into how key institutions manage their websites, and hints and tips on best practice.
Includes bibliographical references and index.
Keywords: Cultural property -- Internet marketing; Web site development; Branding (Marketing)